Analisis Pendapatan Asli Daerah Pada Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun 2016-2021 - Mahmudin, Mahmudin; Saipudin, Saipudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to analyze the Original Local Government Revenue in South Kalimantan during the 2016-2021. The data used in this study is quantitative data. The research method used was data panel regression analysis in South Kalimantan Province. The results of this research analysis show that all independent variables simultaneously and partially have a positive and significant effect on the Original Local Government Revenue variable. and this study also shows the largest contribution of each region in increasing Original Local Government Revenue based on independent variables in this study.